The Use of Group Investigation in Teaching Writing - Yuliarsih, Yuliarsih; Anjarani, Devie Reztia (Journal Prakarsa Paedagogia, 2021)
The objective of the research is to investigate the six steps take place during the process of teaching writing through group investigation and to identify the benefits that the students obtained from writing through group investigation. The results of the study revealed that the teaching writing by using group investigation can improve students’ ability in writing paragraph. Specifically, they showed some improvement on process of writing and vocabulary. Moreover, the data from observation and interview showed that there are some benefits, which are Students build meaningful networks with others who have similar interests, group investigation Created democracy Learning’s Atmosphere, Students were Motivated to Write